Shaping tomorrows: the CCS as agents of change in Europe’s transition - De Smedt, Eva; De Voldere, Isabelle (Frontiers in Communication, 2025)
This article explores the role of the Cultural and Creative Sectors (CCS) as systemic enablers of the European Union’s (EU) triple transition—green, digital and just. It does this by assessing how EU policy frameworks have supported or constrained that role during the 2019–2024 legislative term, and what policy options are needed in the 2024–2029 parliamentary term to more effectively mobilise the CCS as agents of change across EU transition agendas. Drawing on a comprehensive study conducted for the European Parliament’s Committee on Culture and Education (CULT), the article combines critical analysis of EU institutional documents with future-oriented interviews conducted with a dozen policy experts and stakeholders. The concept of the ‘triple transition’ has gained prominence in EU strategic discourse since 2023, adding a social justice dimension to the existing twin focus on climate neutrality and digital innovation. This shift is not merely rhetorical. The discussion argues that the just transition should be understood not as a supplementary concern, but as the very substrate upon which ecological and digital transformation must grow. It calls for a deeper engagement with societal values, participation, and cohesion; areas in which the CCS are uniquely well-positioned to contribute. Yet, this potential remains only partially realised. While policy tools like the New European Bauhaus, the Digital Services Act, Creative Europe, or the European Pillar of Social Rights acknowledge the relevance of the CCS, their operational integration across EU transition strategies remains fragmented. The article identifies critical gaps in funding models, governance coherence, infrastructure, and cross-sectoral collaboration that continue to marginalise cultural actors from key policy arenas. In response, the article proposes a dual strategic approach: first, strengthening the cultural ecosystem through improved working conditions, sustainable finance, and coordinated governance; and second, embedding the CCS more structurally in the design and implementation of transition policies. Through this lens, the article reframes the CCS not as communicative tools but as crucial co-creators of sustainable and democratic futures.